Intergenerational Occupational Mobility in Great Britain and the United States Since 1850: Reply - Long, Jason; Ferrie, Joseph (American Economic Review, 2013)
We respond to several criticisms by Avery Guest and Michael Hout (2013) and Yu Xie and Alexandra Killewald (2013) to Jason Long and Joseph Ferrie (2013). We do not dispute Guest and Hout's characterization of the importance of total mobility in addition to relative mobility. We find much in their additional analyses that supports our original findings. In response to Xie and Killewald, we discuss the limitations of our data and the conceptualization of mobility. (JEL J62, N31, N32, N33, N34)